The Extent of Journalists Reliability on Social Networking Websites as Information Source - Banaz Hama Rashid Hassan; Adel Hama’arif Momin (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This research, titled as The Extent of Journalists’ Reliability on Social Networking Websites as Information Source, includes the problems, objectives, significance and restrictions of researches and samples. The research sample is 95 journalists in Sulaimaniah city. The research also includes practical part, which is comprised of many tables. Following that, some results have been shown. Subsequently, recommendations, suggestions and some points have been disclosed. A question of this research is to realize that to what extent journalists rely on the social networking websites as the source of information and which social networking website they utilize the most. Another purpose is that the researchers intend to find out what benefits journalists get from the social networking websites for their career. It is also an attempt to investigate what the academic, conscience-related and ethical impacts are. Therefore, subsequent to conducting the research both researchers reached several consequences such as, most of participants as journalists for research samples are B.A graduates, and there is a shortage of higher education certificate holders for that. All participants of a research sample use social networking websites, and most of them use Facebook. Most of the social websites benefits are generally to get information. The high usage of the social networking websites as the source of information is moderate. The factor behind sticking to the social networking websites is that they can reach them easily. Publishing false information lies behind dishonesty in publishing information and news. People do not search for information and news in the social networking websites because there is not enough follow-up. The high range of journalists’ social website use is due to their area and career rather than other purposes. The extent of trusting the content of the social networking websites topics is moderate.